Comparison of Cortical and White Matter Traumatic Brain Injury Models Reveals Differential Effects in the Subventricular Zone and Divergent Sonic Hedgehog Signaling Pathways in Neuroblasts and Oligodendrocyte Progenitors. (17th September 2014) - Mierzwa, Amanda J.; Sullivan, Genevieve M.; Beer, Laurel A.; Ahn, Sohyun; Armstrong, Regina C.
The regenerative capacity of the central nervous system must be optimized to promote repair following traumatic brain injury (TBI) and may differ with the site and form of damage. Sonic hedgehog (Shh) maintains neural stem cells and promotes oligodendrogenesis. We examined whether Shh signaling contributes to neuroblast (doublecortin) or oligodendrocyte progenitor (neural/glial antigen 2 [NG2]) responses in two distinct TBI models. Shh-responsive cells were heritably labeled in vivo using Gli1-CreER T2 ;R26-YFP bitransgenic mice with tamoxifen administration on Days 2 and 3 post-TBI. Injury to the cerebral cortex was produced with mild controlled cortical impact. Yellow fluorescent protein (YFP) cells decreased in cortical lesions. Total YFP cells increased in the subventricular zone (SVZ), indicating Shh pathway activation in SVZ cells, including doublecortin-labeled neuroblasts. The alternate TBI model produced traumatic axonal injury in the corpus callosum. YFP cells decreased within the SVZ and were rarely double labeled as NG2 progenitors. NG2 progenitors increased in the cortex, with a similar pattern in the corpus callosum. To further test the potential of NG2 progenitors to respond through Shh signaling, Smoothened agonist was microinjected into the corpus callosum to activate Shh signaling. YFP cells and NG2 progenitors increased in the SVZ but were not double labeled. This result indicates that either direct Smoothened activation in NG2 progenitors does not signal through Gli1 or that Smoothened agonist acts indirectly to increase NG2 progenitors. Therefore, in all conditions, neuroblasts exhibited differential Shh pathway utilization compared with oligodendrocyte progenitors. Notably, cortical versus white matter damage from TBI produced opposite responses of Shh-activated cells within the SVZ.